Research Note: Describing average illuminance for P-class roads. (December 2020) - Fotios, S; Robbins, C
Design criteria for lighting in subsidiary roads usually include a minimum average horizontal illuminance, widely assumed to be the arithmetic mean illuminance. Analyses of the illuminance distributions over thirty road sections shows that the distributions are not normal and hence the median is more appropriate than the arithmetic mean as a measure of central tendency: the medians are significantly lower than the arithmetic means but the two are highly correlated. Design recommendations should state whether it is the arithmetic mean or median and not just the 'average' that is required.